2006
DOI: 10.1182/blood-2005-05-2023
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of molecular-pathway usage in bone marrow homing and its shift by cytokines

Abstract: Efficient bone marrow (BM) homing is a prerequisite for successful engraftment of transplanted hematopoietic cells (HPCs).Contradictory conclusions about the contribution of SDF-1/CXCR4 have clouded our understanding of its role within the molecular pathway cooperation needed for BM homing, particularly with the welldefined hierarchic network of adhesion molecules. In the present study we sought to unravel cooperative and compensatory molecular pathways guiding BM homing. Fresh BM-HPCs, rendered either SDF-1 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 63 publications
7
86
0
5
Order By: Relevance
“…Moreover, homing of HPC refractory to SDF-1 migration is blocked in the absence of a4-integrins, indicating that homing via SDF-1a/CXCR4 can be fully compensated by a functional a4-integrin/VCAM-1 pathway. 94 The enhanced adhesion properties displayed by these GROb-mobilized cells would be consistent with primary reliance on the integrin pathway for homing and engraftment.…”
Section: Chemokine Mobilized Hsc Are Differentmentioning
confidence: 74%
“…Moreover, homing of HPC refractory to SDF-1 migration is blocked in the absence of a4-integrins, indicating that homing via SDF-1a/CXCR4 can be fully compensated by a functional a4-integrin/VCAM-1 pathway. 94 The enhanced adhesion properties displayed by these GROb-mobilized cells would be consistent with primary reliance on the integrin pathway for homing and engraftment.…”
Section: Chemokine Mobilized Hsc Are Differentmentioning
confidence: 74%
“…The preferential effect of GSK3β inhibition on immature versus mature hematopoietic cells is intriguing and led us to search for a unique GSK3β-mediated signaling pathway involved in the motility of immature hematopoietic cells. In line with reports on enhanced migration and homing potential following exposure to SCF (28)(29)(30) and the reduced migratory potential of cKit-deficient immature hematopoietic cells (27), we studied cKit signaling as a potential upstream regulator of GSK3β activity. Indeed, we observed that exposure to SCF enhanced the in vitro migration of HSPCs, especially the more primitive phenotypic HSCs, toward CXCL12 in a GSK3β-dependent manner.…”
Section: Scf Enhances Hspc Migration Via Gsk3βmentioning
confidence: 99%
“…Catecholamines by themselves directly augment the motility of human HSPCs (25). Interestingly, cKit (also termed CD117), which serves as a marker for HSPCs, and its ligand SCF (also termed Kit ligand), are involved in human and murine HSPC motility (26)(27)(28)(29)(30), pointing to a signaling pathway that uniquely regulates the migration of immature hematopoietic cells over mature leukocytes. Moreover, mutant mice with low serum levels of IGF-1 exhibit markedly increased numbers of circulating HSPCs with normal numbers of mature white blood cells (WBCs) (31), pointing to another mechanism by which the egress of immature hematopoietic cells is preferentially regulated.…”
Section: Introductionmentioning
confidence: 99%
“…61 Recent data indicate that CXCL12 may play a role in trafficking ADSCs towards the major pelvic ganglion in rats with an injured cavernous nerve. 62 In our laboratory, we have performed a comparative analysis between ADSCs and BMSCs and were able to show that these two types of MSCs express a similar panel of chemokine receptors. We identified expression of mRNA for 12 of the currently known 21 chemokine receptors, and found that these receptors were located both on the cell surface as well as intracellularly, suggesting that chemokine receptors are recycled in these stem cells, as has been previously shown in various immune cells (unpublished data).…”
Section: Trafficking Of Exogenously Administered Stem Cellsmentioning
confidence: 99%
“…[58][59][60][61][62][63] Rolling and firm adhesion is followed by transendothelial migration across the physical endothelium/extracellular matrix barrier.…”
Section: Trafficking Of Exogenously Administered Stem Cellsmentioning
confidence: 99%